Workforce Sustainability in Maine’s Coastal Industries: Strategies to Diversify, Train, and Bolster the Workforce - Picard, Jessica (Maine Policy Review, 2023)
People living in Maine have been working the oceans and related industries for hundreds of years. It is crucial to ensure that jobs along the coast are sustainable for years to come. This article examines the importance of job quality, including wages, safe working conditions, and opportunities to advance, along with the ways that some industries are utilizing programs with these ideas in mind - such as the country’s first registered apprenticeship program in aquaculture, which is now underway in Maine.